The Summer People - West, John Foster (Appalachian State University, 1989)
In the summer of 1974, twenty-four year old Anna DeVoss finds herself widowed and alone in the unfamiliar country of the North Carolina mountains. The body of her husband, a navy pilot missing in action for six years, has just been returned home from Vietnam. Following his funeral her mother in law persuades her to spend some time alone at the family's summer home in Watauga County, North Carolina, in what becomes a summer of discovery for Anna.